COP27 Climate Change Conference: Urgent Action Needed for Africa and the World - Ofori-Adjei, David; Zielinski, Chris; Zakhama, Lilia; Yonga, Paul; Yassien, Mohammad Sahar; Tumwine, James; Snouber, Abdelmadjid; Sidibé, Siaka; Rashidian, Arash; Okonofua, Friday; et al. (Cerrahpaşa Medical Journal, 2022)
Cite this article as: Atwoli L, Erhabor GE, Gbakima AA, et al. COP27 Climate Change Conference: Urgent action needed for Africa and the world. Cerrahpaşa Med J. 2022;46(3):181-182.